Relationship between Liquidity Management and Growth of MSMEs in Africa: A Case Study of Selected Districts of Uganda - Mayanja, Sazir Nsubuga; Mayanja, Shakira Namutebi (American Journal of Finance, 2020)
Purpose: The study set out to establish to what extent, if any, a relationship exists between liquidity management and growth of MSMEs in Africa, with Uganda as a case study. Methodology: The study used a combination of cross sectional and descriptive designs in which both qualitative and quantitative approaches were adopted. Questionnaires were administered to respondents who answered both open-ended and close-ended questions. Quantitative data was analysed by means of frequencies, percentages, regression analysis and means correlations to arrive at conclusions. The qualitative aspect of the research was intended to clarify the quantitative findings and data. A sample of 400 respondents was chosen from four districts of Wakiso, Mukono, Kampala and Jinja using random sampling. A sample of 400 was chosen from four districts of Wakiso, Mukono, Kampala and Jinja. Of these 371 responded. This represents a satisfactory response rate of over 92%. Findings: This relationship was confirmed by ANOVA results of a large F- Value (23.215) and small significance level (P or 0.000<0.05). Conclusion from the research is that there is a significant relationship between management of liquidity and growth of MSMEs in Uganda Unique Contribution to Practice and Policy: It is recommended that MSMEs review modes of financing liquidity requirements. It is further recommended that MSMEs should practice effective cash planning and investment of surplus funds in ways and manner that enhance the capital, and consequently, growth of the firms. The results of the study should provide very useful input for policy makers, SME managers and owners while making to enhance growth of MSMEs. It is also useful for researchers and academics